Small pelagic fish fitness relates to local environmental conditions and trophic variables. (March 2022) - Lloret-Lloret, E.; Albo-Puigserver, M.; Giménez, J.; Navarro, J.; Pennino, M.G.; Steenbeek, J.; Bellido, J.M.; Coll, M.
Highlights: Two small pelagic species showed spatial and seasonal variations in fitness at local scales. Changes were mostly explained by environmental variables while spatial and seasonal factors were important. Trophic variables also contributed, suggesting that variations in prey abundance, composition and quality can impact their fitness. Results underline the potential vulnerability of SPF to local spatiotemporal environmental changes. Abstract: Small pelagic fish (SPF) are key organisms for the functioning of pelagic marine ecosystems. In recent decades, these species have undergone significant changes in biomass, growth and body condition in the Mediterranean Sea. Seasonal and spatial information about changes in biological and ecological traits of SPF and their relationship with environmental variables is still missing. Here, we have investigated along a latitudinal gradient in the Northwestern Mediterranean Sea the seasonal patterns of fish fitness (in terms of body condition, fat content and reproduction activity) of two important Mediterranean SPF, European anchovy ( Engraulis encrasicolus ) and European sardine ( Sardina pilchardus ). We used non-parametric multivariate analyses and Generalized Additive Models (GAMs) to investigate which environmental and trophic variables could explain observed variations during 2018–2019. Mean fat content values, relative condition index (Kn ) and gonadosomatic index (GSI) were calculated monthly. We also measured individual's stable isotope composition in muscle. Chlorophyll-a, sea surface temperature and salinity were used as environmental descriptors. The results revealed spatial and temporal variations for both species in terms of body condition, fat content and reproduction indices, as well as of stable isotopic values. GAMs showed that the variability in fitness for both species was mostly explained by environmental variables, in addition to the spatial and seasonal factors. Trophic variables contributed to explain the variability of the indices, mostly in the case of anchovy. This study provides insights into the spatial and seasonal interplay of the fitness of two important commercial species along a latitudinal gradient, and contributes to understand the fluctuations of SPF population and recent declining trends to inform proactive fisheries management at local and regional scale.